2011
DOI: 10.1111/j.1365-2559.2011.03757.x
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B kinase expression in laryngeal squamous cell carcinoma and its prognostic implications

Abstract: International audienceAims: To investigate the clinical and prognostic significance of Aurora B in laryngeal squamous cell carcinomas (LSCC). Methods and results: Aurora B protein expression was analyzed in a series of 259 LSCC. In addition, the expression of the proliferation index (Ki67) and other proteins involved in cell cycle control, such as Aurora A, survivin and p53 was also determined. Aurora B was highly expressed in 55.4% of LSCC. High Aurora B expression levels were correlated with tumour recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…Univariable analysis showed high AURKB and GMNN PI to be associated with a significantly worse prognosis in terms of OS and EFS, in agreement with publicly available NB gene expression array data (R2: microarray analysis and visualization platform (http://r2.amc.nl)). Our data are also in line with studies that showed an association between increased immunohistochemical expression of AURKB and shorter survival in head and neck [31], laryngeal [32], lung [33], hepatocellular [34], biliary tract [35], endometrial [36], and ovarian cancer [37]. Similarly, our results are consistent with association between high GMNN level and shorter survival in breast [38], penile [39], renal cell [40], and other cancers, reviewed by Kapoor [41] and Petropoulou et al [20].…”
Section: Discussionsupporting
confidence: 95%
“…Univariable analysis showed high AURKB and GMNN PI to be associated with a significantly worse prognosis in terms of OS and EFS, in agreement with publicly available NB gene expression array data (R2: microarray analysis and visualization platform (http://r2.amc.nl)). Our data are also in line with studies that showed an association between increased immunohistochemical expression of AURKB and shorter survival in head and neck [31], laryngeal [32], lung [33], hepatocellular [34], biliary tract [35], endometrial [36], and ovarian cancer [37]. Similarly, our results are consistent with association between high GMNN level and shorter survival in breast [38], penile [39], renal cell [40], and other cancers, reviewed by Kapoor [41] and Petropoulou et al [20].…”
Section: Discussionsupporting
confidence: 95%
“…Very recently, García‐Fernández et al. 23 determined survivin, Aurora B, Aurora A and p53 expressions in a large series of 259 LSCCs. Survivin expression was assessable in 234 cases: 100% of the cases showed cytoplasmic survivin expression and 45% a nuclear‐cytoplasmic pattern.…”
Section: Discussionmentioning
confidence: 99%
“…) of aurora‐A and aurora‐B were clearly detected by RT‐PCR and western blots. In humans, over‐expression of aurora‐A and/or aurora‐B has been suggested as prognostic markers in some types of malignant tumours . Quantification of the mRNA between malignant tumours, and investigating its relationship to the treatment response and/or prognosis would be a useful next step.…”
Section: Discussionmentioning
confidence: 99%